Peningkatan Hasil Belajar Pendidikan Agama Islam Dengan Menerapkan Model Pembelajaran PAKEM - Situmorang, Swita Hasriana (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The purpose of this study was to determine the improvement in student learning outcomes after the implementation of the PAKEM learning model. This research uses action research as many as three rounds. The targets of this study were fourth grade students, SD Negeri 4 Janji Martahan, Harian sub-district, Samosir district in the 2019/2020 school year. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning outcomes increased from cycle I to cycle III, namely, cycle I (68.00%), cycle II (80.00%), cycle III (92.00%). The conclusion of this study is that the PAKEM learning model can have a positive effect on the learning motivation of grade VI students of SD Negeri 4 Janji Martahan, and this learning model can be used as an alternative to learning Islamic religious education. Keywords: PAKEM; the story of the prophet Abstrak: Tujuan dari penelitian ini untuk mengetahui peningkatan hasil belajar siswa setelah diterapkannya model pembelajaran PAKEM. Penelitian ini menggunakan penelitian tindakan (action research) sebanyak tiga putaran. Sasaran penelitian ini adalah siswa kelas IV, SD Negeri 4 Janji Martahan, kecamatan Harian, kabupaten Samosir tahun pelajaran 2019/2020. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analis didapatkan bahwa hasil belajar siswa mengalami peningkatan dari siklus I sampai siklus III yaitu, siklus I (68,00%), siklus II (80,00%), siklus III (92,00%). Simpulan dari penelitian ini adalah model pembelajaran PAKEM dapat berpengaruh positif terhadap motivasi belajar siswa kelas VI SD Negeri 4 Janji Martahan, serta model pembelajaran ini dapat digunakan sebagai salah satu alternatif pembelajaran Pendidikan Agama .Islam. Kata Kunci: kisah nabi; PAKEM